"Rewriting and redefining Utopia; minorities' perfect existence or ultimate destruction" - Le Grange, Jason John (Department of English Language and Literature, 2014)
Utopia as a construct within an ideology offers minority groups a feasible space from which to negotiate an identity within a dominant discourse. Continuing human atrocities have led to a âspiral of oppressionâ, in which oppression continues, never resolving itself and never diminishing, but rather moving away from the utopian space within the centre. As the dominant discourse is threatened by the minority, minority groups are placed spatially, within this spiral of oppression into a marginal position called the âuniversal minorityâ, from which they have to negotiate with the dominant discourse, the âuniversal majorityâ, however unsuccessfully. Science fiction and utopian writing offer spaces in which minority groups can break through the âspiral of oppressionâ and negotiate directly with the dominant discourse. Trends in these two genres reveal which group is visioned as the âuniversal minorityâ, and the plight of the minority is highlighted in the alternative reality of these genres. Race (focussing on Hispanic discourse) and Sexuality (focussing on viable spaces for alternative sexuality) are two areas which are explored in this thesis as visions of the universal minority. Moreover, to understand the spiral of oppression, the Holocaust is reflected upon from a minority perspective, and literary responses as well as issues of post-holocaust compensation are addressed, reflecting the nature of the universal majority and universal minority. Finally, Utopia is often considered an unrealistic construct which cannot be attained by any legitimate agency other than an oligarchist regime or a strict governing body, which could lead to tyranny. Agency therefore is problematic; however, it will be argued that, even if full Utopia is not reached, the spiral of oppression can be broken and a utopian bridge of opportunity created through an idea of Brechtâs called Verfremdungseffekt (prompting self-awareness), using the South African Truth and Reconciliation Commission as an example of a vehicle for this agency. The agency then becomes the awareness, which leads to the direct negotiation with the dominant discourse.